An edge detection method using outer totalistic cellular automata - Amrogowicz, Sebastian; Zhao, Yitian; Zhao, Yifan (Elsevier, 2016)
A number of Cellular Automata (CA)-based edge detectors have been developed recently due to the simplicity of the model and the potential for simultaneous removal of different types of noise in the process of detection. This paper introduced a novel edge detector using Outer Totalistic Cellular Automata. Its performance has been compared with other recently developed CA-based edge detectors, in addition to some classic methods, through testing images from a public library. Visual and quantitative measurement of similarity with manually marked correct edges confirmed the superiority of the proposed method over conventional and state-of-the-art CA-based edge detectors.
Keywords: Cellular Automata; Edge detection; Figure of merit; Totalistic Cellular Automata